Caves as interim-refugia: Chemical signatures of human habitation under extreme environments of Ladakh, NW India. (April 2021) - Chaddha, Amritpal Singh; Mathews, Runcie P.; Kumar, Kamlesh; Ali, Sheikh Nawaz; Phartiyal, Binita; Manoj, M.C.; Sharma, Anupam
Graphical abstract: Highlights: Chemical characterization of black charred material of cave roof manifest anthropogenic origin. Polyaromatic hydrocarbons (PAH) confirm graphitic character (soot), implying burning origin. Caves offered an interim-refugia to the transhumant herder people and travelers along silk route. Abstract: Caves – particularly in the Eastern part of Ladakh – offered interim-refugia to the transhumant herders and travelers during different times (and climates) in the past. The past communities living in the extreme environmental conditions of Ladakh followed a transhumance lifestyle and combined it with subsistence agriculture for living. In order to better understand how ancient people utilised the caves located in eastern sector of Ladakh along the Leh-Manali route, we systematically surveyed a number of caves which contain archaeological traces of Transhumant occupation. The ceilings of most of the caves have coatings of a very hard, sticky, shiny, and resinous Black Charred Material (BCM). Multiple analysis using X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy (FESEM-EDX), FourierTransform -Infrared Spectroscopy (FT-IR), Raman Spectroscopy, Gas Chromatography-Mass Spectroscopy (GC–MS), Lassaigne's test, elemental and stable isotope analysis of carbon and sulfur using Element- Analyser coupled with Isotopic Ratio- Mass Spectroscopy (IR-MS) were applied to characterize the cave roof coatings. The results indicate presence of quartz > plagioclase > dolomite (sandstone) type host rock in the vicinity, whereas, the BCM shows graphitic moiety. The completely different diffractograms of host rock and BCM suggest that there is no genetic relationship, where the substrate is of natural lithogenic origin, while the BCM is anthropologically produced. Similarly, polyaromatic hydrocarbons (PAHs) peaks in the D and G band confirm the graphitic character of anthropogenic origin. The higher concentration of PAHs in soot particles, which are carcinogenic in nature may severely affect human health. The high average wind speed containing relatively large quantities of silica particles, along with increased PAHs, may be responsible for the non-occupational pneumoconiosis prevalent in the region. Based on these observations, we hypothesize that the caves were used by the transhumant herder communities during the summer for grazing their livestock and by travelers during the long silk route journeys.